KINETIC AND ACTIVATION PARAMETERS FOR THE REDUCTION OF DIPHENYLBENZIDINE WITH ASCORBIC ACID - Perveen, Abida; Naqvi, I. I. (The Nucleus, 2020)
In order to get an insight into the activation parameters, rate of the reaction between ascorbic acid (ASC) and diphenylbenzidine (DPBD) was studied. The reactants were mixed in four different ratios (1:10, 1:15, 1:20 and 1:25) and the rate was determined at temperatures of 15oC, 20oC, 25oC and 30oC by measuring absorbance of the violet solution (DPBD) at ï¬max = 570 nm. Diphenylbenzidine (DPBD) was prepared by mixing diphenylamine and cerium (IV) sulfate tetrahydrate solutions in a ratio of 1:2. The pseudo first order rate constants, kobs , thus obtained was used to calculate the second order rate constant, kÂ´ = kobs / [DPBD] . The activation energy of the reaction was determined using Arrhenius equation and was found to be 30.00 Â± 0.56 kJ mol-1. Other activation parameters, Î”Sâ‰ and Î”Hâ‰ , were calculated from the slope and intercept of Eyring equation obtained from a plot of ln (kÂ´/T) against inverse temperature, (1/T). Entropy of activation Î”Sâ‰ has been found to be â€“ 99Â±0.05 J mol-1 K-1 and that Î”Hâ‰ was 28.00Â±0.34 kJ mol-1.